Cardiovascular Recovery From Psychological and Physiological Challenge and Risk for Adverse Cardiovascular Outcomes and All-Cause Mortality. Issue 3 (April 2015) - Panaite, Vanessa; Salomon, Kristen; Jin, Alvin; Rottenberg, Jonathan
ABSTRACT Objective Exaggerated cardiovascular (CV) reactivity to laboratory challenge has been shown to predict future CV morbidity and mortality. CV recovery has been less studied and has yielded inconsistent findings, possibly due to the presence of moderators. Reviews on the relationship between CV recovery and CV outcomes have been limited to cross-sectional studies and have not considered methodological factors. We performed a comprehensive meta-analytic review of the prospective literature investigating CV recovery to physical and psychological challenge and adverse CV outcomes. Methods We searched PsycINFO and PubMed for prospective studies investigating the relationship between CV recovery and adverse CV outcomes. Studies were coded for variables of interest and for effect sizes. We conducted a random-effects weighted meta-analysis. Moderators were examined with analysis of variance–analog and meta-regression analyses. Results Thirty-seven studies met the inclusion criteria (n = 125, 386). Impaired recovery from a challenge predicted adverse CV outcomes (summary effect, r = 0.17, p < .001). Physical challenge was associated with larger predictive effects than psychological challenge. Moderator analyses revealed that recovery measured at 1 minute postexercise, passive recovery, use of mortality as an outcome measure, and older sample age were associated with larger effects. Conclusions Poor recovery from laboratory challenges predicts adverse CV outcomes, with recovery from exercise serving as a particularly strong predictor of CV outcomes. The overall effect size for recovery and CV outcomes is similar to that observed for CV reactivity and suggests that the study of recovery may have incremental value for understanding adverse CV outcomes.